Chronic alcohol consumption increases inflammation and osteoclastogenesis in apical periodontitis - Dal-Fabbro, R. [UNESP]; Marques-de-Almeida, M. [UNESP]; Cosme-Silva, L. [UNESP]; Ervolino, E. [UNESP]; Cintra, L. T.A. [UNESP]; Gomes-Filho, J. E. [UNESP] (Wiley, 2019)
Aim: To investigate the effect of chronic alcohol consumption on apical periodontitis in rats. Methodology: Thirty-two male Wistar rats were arranged into four groups: Control (C): without apical periodontitis and nonalcoholic diet; (AL): without apical periodontitis and alcoholic diet; (AP): with apical periodontitis and nonalcoholic diet; and (AP + AL): with apical periodontitis and alcoholic diet. The alcoholic solution at 20% was given to the AL and AP + AL groups as the sole source of hydration throughout the experiment. AP was induced in the mandibular left first molars at the end of the 4th week. Weight changes and the amount of solid and liquid foods were recorded for 8 weeks. At the end, the animals were euthanized and the jaws removed followed by histological processing for histopathological and RANKL, OPG, TRAP and HIF-1α analyses. The Mann–Whitney test was used for nonparametric data, and anova followed by the Tukey test was performed for parametric data, with P < 0.05. Results: Animals that received the alcoholic diet had a lower weight gain than the other groups (P < 0.05). Control and AL groups did not have an inflammatory response in the periapical tissues. The median score of inflammatory infiltrate was significantly higher in the AP + AL group (2.5) compared to the AP group (1.5; P < 0.05). In the same comparison, AP + AL was associated with score 3 for RANKL and HIF-1α versus score 2 for AP group (P < 0.05). Moreover, the values for TRAP were 3.88 ± 0.70 cells mm−1 for the AP + AL group and 2.43 ± 0.94 cells mm−1 for the AP group (P < 0.05). Conclusion: In rats, an alcoholic diet had a significant effect on the severity of apical periodontitis, exacerbating the inflammatory response and osteoclastogenesis.
Keywords: alcoholism; apical periodontitis; endodontics